Refining the Global Spatial Limits of Dengue Virus Transmission by Evidence-Based Consensus - Brady, Oliver J.; Gething, Peter W.; Bhatt, Samir; Messina, Jane P.; Brownstein, John S.; Hoen, Anne G.; Moyes, Catherine L.; Farlow, Andrew W.; Scott, Thomas W.; Hay, Simon I. (PLOS Neglected Tropical Diseases, 2012)
Author Summary Previous attempts to map the current global distribution of dengue virus transmission have produced variable results, particularly in Africa, reflecting the lack of accuracy in both diagnostic and locational information of reported dengue cases. In this study, instead of excluding these less informed points we included them with appropriate uncertainty alongside other diverse evidence forms. After assembling a comprehensive database of different evidence types, a weighted scoring system calculated “evidence consensus” for each country a continuous measure of the certainty of dengue presence or absence when considering the full aggregate of evidence. The resulting map and analysis helped highlight important evidence gaps that underlie uncertainties in the current distribution of dengue. We also show the importance of local knowledge through incorporating questionnairebased responses that can help add clarity in uncertain regions. This analysis showed that presence/absence maps do not sufficiently highlight the uncertainties in the evidence base used to construct them. Mapping by evidence consensus not only encourages greater data inclusion, but it also better illustrates the current global distribution of dengue. Consensus mapping is thus ideal for a range of neglected tropical diseases where the evidence base is incomplete or less diagnostically reliable.